Effects of medicated and non-medicated multi-nutrient block supplementation on gastrointestinal parasite infestation and blood hematological parameters of lactating saanen goats - Mira Panadi,; Wan Zahari Mohamed,; Nor Dini Rusli,; Khairiyah Mat, (Penerbit Universiti Kebangsaan Malaysia, 2018)
In a 90-day feeding trial, twenty four (24) Saanen lactating does were assigned to four treatment group. The treatments were feeding: basal diet only as a control (T1), basal diet with urea molasses multi-nutrient block (UMMB) (T2), basal diet with medicated urea molasses multi-nutrient block (MUMB) (T3) and basal diet with commercial mineral block (CMB) (T4). There were significant differences (p<0.05) between T2, T3 and T4 on the fecal egg count (FEC). Animals in T2 and T3 showed moderate level of parasite infestation i.e. at 750 epg and 950 epg, respectively, while animals in T1 and T4 showed severe parasite load at 4917 epg and 1850 epg, respectively. There were no significant differences (p>0.05) between treatments on WBC, LYM, MON, GRA, RBC, HCT, MCV, MCH, PLT, MPV and PCT. However, significant effects (p<0.05) on HBG, MCHC, RDW and PDW were observed in T2 and T3. This research showed that UMMB and MUMB were effective in controlling parasite infestation in Saanen lactating dairy goats apart from improving their blood hematological parameters. Comparison with CMB showed that it is practical to be used for parasite control.